Transformers [ - Bay, Michael; DeSanto, Tom; Kurtzman, Alex; Orci, Robert; Rogers, John (Paramount, 2007)
On the planet Cybertron, a war was waged between the Autobots and the Decepticons for control of the Allspark, a mystical talisman that would grant unlimited power to whoever possessed it. The Allspark is smuggled off the planet, but Megatron goes in search of it. He tracks it to Earth and his desire for power sends him into the Arctic Ocean. The sheer cold forces him into a paralyzed state. His body is later recovered, and before going into a comatose state he uses the last of his energy to engrave a map, showing the location of the Allspark, into the Captain's glasses. A century later, Spike buys his first car. To his shock, he discovers it is an Autobot in disguise. He is to protect Spike, who bears the Captain's glasses. Other Transformers have arrived In the desert of Qatar and the Decepticons attack a U.S. military base. Spike and his girlfriend Mikaela find themselves in the middle of a grand battle between the Autobots and the Decepticons. Meanwhile, within the depths of Hoover Dam, the cryogenically stored form of Megatron awakens.